Foreign Exchange Reserve in India - A Review - Amsaveni, R.; Geetha, S. (Indian Journal of Finance, 2007)
The term Foreign Exchange is used to indicate the exchange of one currency for another and also denotes a foreign currency. The importing currency pays money to exporting in return of goods either in its domestic currency or hard currency. The currency, which facilitates the payment to complete the transaction, is called foreign exchange. Foreign exchange is bought and sold in foreign exchange markets. The components of foreign exchange market include buyers, sellers and intermediaries in foreign exchange market. It is the market for currencies of various countries any- where in globe, as financial centers of world are united as a single market.